Isolated, neglected, and likely threatened: a new species of Magoniella (Polygonaceae) from the seasonally dry tropical forests of Northern Colombia and Venezuela revealed from nuclear, plastid, and morphological data - Aguilar-Cano, J; Pérez-Escobar, OA; Pizano, C; Tovar, E; Antonelli, A (Frontiers Media, 2024)
Seasonally tropical dry forests (SDTFs) in the American tropics are a highly diverse yet poorly understood and endangered ecosystem scattered from Northern Mexico to Southern Argentina. One floristic element of the STDFs is the genus Magoniella (Polygonaceae), which includes two liana species, M. laurifolia and M. obidensis, which have winged fruits and are distributed from Costa Rica to Southern Brazil. In a field expedition to the SDTFs of the Colombian Caribbean in 2015, morphologically distinctive individuals of Magoniella were found. In this study, we investigated the species boundaries within Magoniella and determined the phylogenetic position of these morphologically distinctive individuals in the tribe Triplaridae. We compiled morphological trait data across 19 specimens of both species and produced newly sequenced nuclear–plastid DNA data for M. obidensis. Morphometric analyses revealed significant differences in fruit length and perianth size among individuals from the Colombian Caribbean compared to M. obidensis and bract length when compared to M. laurifolia. Maximum likelihood analysis of non-conflicting nuclear and plastid datasets placed the Colombian Caribbean individuals as sister to M. obidensis with maximum statistical support. Additionally, pairwise sequence comparisons of the nuclear ribosomal ITS and the lfy2i loci consistently showed 15-point mutations (10 transitions, five transversions) and six 2 bp-long substitutions that differ between M. obidensis and the Colombian Caribbean individuals. Our morphological and molecular evidence thus suggests that the Colombian Caribbean individuals of Magoniella represent a divergent population from M. laurifolia and M. obidensis, which we describe and illustrate as a new species, M. chersina. Additionally, we provide nomenclatural updates for M. laurifolia and M. obidensis. This study highlights the power of combining morphological and molecular evidence in documenting and naming plant diversity.